PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kusumawati, Nugrahini; Afiah, Efi Tajuroh; Yuliyanti, Putri (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2023)
The company's financial performance declined due to one of the reasons for the slowdown in household consumption. In the first quarter of 2019, consumption growth was 5.01% on an annual basis. Consumption slowed slightly from the fourth quarter of 2018 which reached 5.08%. This study aims to analyze the influence of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on the company's financial performance. The measurement of corporate social responsibility is based on the Global Reporting Initiative (GRI) disclosure index as seen from the company's annual report. The method used in this research is associative quantitative research. Associative quantitative is research that is asking the relationship between two or more variables. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDK) 2017-2021. The research sample was taken using purposive sampling technique and obtained 8 companies, with observations for 5 years. So, the number of samples studied is 40. The results of this study indicate that the mechanism of Good Corporate Governance (GCG), namely institutional ownership has no significant effect on the company's financial performance which is reflected in the return on assets (ROA). Meanwhile, Corporate Social Responsibility (CSR) has a significant effect on the company's financial performance on return on assets (ROA).